2021
DOI: 10.17219/acem/133485
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 induces senescence of leukemic stem cells by upregulating p16INK4a and downregulating hTERT expression

Abstract: Background. Leukemic stem cells (LSCs) play an important role in the pathogenesis of leukemia. This research attempted to clarify effects of the telomere system on ginsenoside Rg1-induced senescence of LSCs.Objectives. This research attempted to clarify effects of the telomere system on ginsenoside Rg1-induced senescence of LSCs.Materials and methods. CD34 + CD38 − LSCs were isolated, sorted, and divided into a control group and a Rg1 group (treated with 40 μmol/L Rg1). Cell Counting Kit-8 (CCK-8) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ginsenoside Rg1 (Rg1) is a bioactive substance that can be found in the roots of ginseng (Panax ginseng) and turned white or red ginseng [124,125]. Rg1 has a hepatoprotective effect, promotes cerebral angiogenesis and lymphatic drainage, improves chronic inflammatory arthritis, and prevents PTSD-like behaviors [126][127][128][129].…”
Section: Saponinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenoside Rg1 (Rg1) is a bioactive substance that can be found in the roots of ginseng (Panax ginseng) and turned white or red ginseng [124,125]. Rg1 has a hepatoprotective effect, promotes cerebral angiogenesis and lymphatic drainage, improves chronic inflammatory arthritis, and prevents PTSD-like behaviors [126][127][128][129].…”
Section: Saponinsmentioning
confidence: 99%
“…Rg1 has a hepatoprotective effect, promotes cerebral angiogenesis and lymphatic drainage, improves chronic inflammatory arthritis, and prevents PTSD-like behaviors [126][127][128][129]. A study on CD34+CD38− leukemic stem cells (LSC) showed that Rg1 down-regulates the expression of hTERT and up-regulates p16 INK4a (a protein that slows down the cell cycle) expression, which causes senescence of LSC [124]. Another study, using Korean red ginseng (KRG) on U937 cells, showed its anti-cancer properties.…”
Section: Saponinsmentioning
confidence: 99%
“…Rg1 has a hepatoprotective effect, promotes cerebral angiogenesis and lymphatic drainage, improves chronic inflammatory arthritis, and prevents PTSD-like behaviors [92,93,94,95]. A study on CD34+CD38− leukemic stem cells (LSC) showed, that Rg1 downregulates the expression of hTERT and upregulates p16 INK4a (protein, that slows down the cell cycle) expression, which causes senescence of LSC [104]. Another study, using Korean red ginseng (KRG) on U937 cells showed its anti-cancer properties.…”
Section: Other Substancesmentioning
confidence: 99%
“…This enhanced telomerase activity may be an adaptive mechanism aimed at maintaining the continuous replication of LSCs and promoting leukemia development ( Kuo and Bhatia, 2014 ). A recent study found that ginsenoside Rg1 inhibited CD34 + CD38-LSCs proliferative activity, increased expression of telomere damage effector p16 INK4a , and decreased human telomerase reverse transcriptase (hTERT, catalytic subunit of telomerase) to induce its replicative senescence for the treatment of leukemia ( Tang et al, 2021 ). The above findings suggest that ginsenoside Rg1 inhibits the ability of LSCs to self-renewal and proliferation, and its targeted therapy based on the intervention of LSCs senescence is a valuable direction for healing leukemia in the future.…”
Section: Effects Of Ginseng On Different Types Of Stem Cellsmentioning
confidence: 99%